1991
DOI: 10.2307/256404
|View full text |Cite
|
Sign up to set email alerts
|

People and Organizational Culture: A Profile Comparison Approach to Assessing Person-Organization Fit.

Abstract: This article brings together three current themes in organizational behavior: (1) a renewed interest in assessing person-situation interactional constructs, (2) the quantitative assessment of organizational culture, and (3) the application of "Q-sort," or template-matching, approaches to assessing person-situation interactions. Using longitudinal data from accountants and M.B.A. students and cross-sectional data from employees of government agencies and public accounting firms, we developed and validated an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

62
1,741
5
62

Year Published

1996
1996
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 3,045 publications
(1,870 citation statements)
references
References 73 publications
62
1,741
5
62
Order By: Relevance
“…Outros estudos chamam a atenção para a importância do conteúdo das táticas de socialização como uma forma eficaz de promover a adequação dos valores individuais e organizacionais (Cable & Parson, 2001;O'Reilly, Chatman, & Caldwell, 1991). A socialização é compreendida como uma troca que ocorre por meio de atividades conjuntas, tais como conviver em um mesmo ambiente, manter conversas interativas e compartilhar conhecimento e experiências (Chang, Huang, Chiang, Hsu, & Chang, 2012).…”
Section: Referencial Teóricounclassified
See 1 more Smart Citation
“…Outros estudos chamam a atenção para a importância do conteúdo das táticas de socialização como uma forma eficaz de promover a adequação dos valores individuais e organizacionais (Cable & Parson, 2001;O'Reilly, Chatman, & Caldwell, 1991). A socialização é compreendida como uma troca que ocorre por meio de atividades conjuntas, tais como conviver em um mesmo ambiente, manter conversas interativas e compartilhar conhecimento e experiências (Chang, Huang, Chiang, Hsu, & Chang, 2012).…”
Section: Referencial Teóricounclassified
“…A segunda parte do questionário é composta por questões desenvolvidas por O'Reilly e Chatman (1986) para medir o nível de adequação dos valores individuais com os valores organizacionais. Pesquisas anteriores reportam alta confiabilidade e validade do instrumento com uma confiabilidade média de 0,76 (O'Reilly et al, 1991). Os itens do questionário estão descritos no Apêndice.…”
Section: Coleta De Dadosunclassified
“…In contrast, the literature presents "commensurate measurement" which enables the implementation of a common standard to measure personal and organizational values (Chatman, 1989). The popular instruments used for commensurate measurement include: the Organizational Culture Profile (OCP; O'Reilly, Chatman and Caldwell, 1991) The values' assessment is an embryonic topic in the context of construction industry. Although some scholars particularly focused on personal values of construction participants (e.g., Munson and Posner, 1979;Daniela et al, 2013), nonetheless the study by Thomson and Austin (2006) can be considered as the most specific attempt to assess values in construction projects.…”
Section: Personal-organisational Valuesmentioning
confidence: 99%
“…Previous research has focused on the impact of religious values in the workplace and found that the predominant religious values have an immense impact on people's emotional responses (Locke, 1976) and on the decision making and actions of members of an organisation (O'Reilly, Chatman, & Caldwell, 1991). For instance, O'Reilly et al (1991) found that individual variations in preferences for different organisational cultures are profoundly related to individuals' personality characteristics, by analysing longitudinal data from accountants and MBA students, and cross-sectional data from employees of government agencies and public accounting firms.…”
mentioning
confidence: 99%
“…For instance, O'Reilly et al (1991) found that individual variations in preferences for different organisational cultures are profoundly related to individuals' personality characteristics, by analysing longitudinal data from accountants and MBA students, and cross-sectional data from employees of government agencies and public accounting firms. They also emphasised the importance of understanding the fit between individuals' preferences and organisational cultures for better organisational effectiveness.…”
mentioning
confidence: 99%